2007
DOI: 10.1002/acp.1380
|View full text |Cite
|
Sign up to set email alerts
|

Summarizing digital documents: effects of alternate or simultaneous window display

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Note that increasing use of computer displays (and increasing use of laptops) tends to push complex tasks into stacked formats because the available screen real estate tends to be smaller than what a problem solver has available in the physical world (e.g., he or she can spread out a stack of paper on a desk or pin multiple papers up on a wall; even compare the space available on a small laptop screen, iPhone, or iPad relative to a larger desktop monitor). The benefit of spatially distributed task materials over stacked displays has also been reported in studies of multimedia learning (Olive, Rouet, François, & Zampa, 2008;Wiley, 2001). Olive et al (2008) tested the effect of display format on a summarizing activity and found that the alternative display-corresponding to the stacked display in our framework-of source documents and notepad increased the cognitive load of the summarizing activity.…”
Section: Considering Another Variation Of Spatial Layoutmentioning
confidence: 94%
See 2 more Smart Citations
“…Note that increasing use of computer displays (and increasing use of laptops) tends to push complex tasks into stacked formats because the available screen real estate tends to be smaller than what a problem solver has available in the physical world (e.g., he or she can spread out a stack of paper on a desk or pin multiple papers up on a wall; even compare the space available on a small laptop screen, iPhone, or iPad relative to a larger desktop monitor). The benefit of spatially distributed task materials over stacked displays has also been reported in studies of multimedia learning (Olive, Rouet, François, & Zampa, 2008;Wiley, 2001). Olive et al (2008) tested the effect of display format on a summarizing activity and found that the alternative display-corresponding to the stacked display in our framework-of source documents and notepad increased the cognitive load of the summarizing activity.…”
Section: Considering Another Variation Of Spatial Layoutmentioning
confidence: 94%
“…The benefit of spatially distributed task materials over stacked displays has also been reported in studies of multimedia learning (Olive, Rouet, François, & Zampa, 2008;Wiley, 2001). Olive et al (2008) tested the effect of display format on a summarizing activity and found that the alternative display-corresponding to the stacked display in our framework-of source documents and notepad increased the cognitive load of the summarizing activity. While participants wrote a summary, they were also asked to perform a secondary task (i.e., responding to randomly spaced auditory tones).…”
Section: Considering Another Variation Of Spatial Layoutmentioning
confidence: 94%
See 1 more Smart Citation
“…However, some researchers claim that digital reading has several drawbacks. Olive and Rouet (2008) claimed that digital reading is suboptimal and less effective than paper reading. Liu (2005) found that during digital reading, less time is spent on in-depth reading, and sustained attention.…”
Section: Instructional Resourcesmentioning
confidence: 99%
“…First of all, the screen induces digital reading that provides different experiences than reading on paper [5]. Second, the size of the screen may make it difficult to simultaneously view a source document and write another document [6]. Further, the virtual keyboard of the tablet may reduce screen visibility [7].…”
Section: Introductionmentioning
confidence: 99%